Guidelines for open pit slope design - Read, John; Stacey, Peter (CRC Press/Balkema, 2009)
Suitable for open pit mine slope design practitioners, including engineering geologists, geotechnical engineers, mining engineers and civil engineers and mine managers, this book helps them in meeting stakeholder requirements for pit slopes that are stable, in regards to safety, ore recovery and financial return, for the required life of the mine